STEAM EDUCATION AS FUTURE EDUCATION: SCIENTIFIC THEORETICAL BASIS OF USING STEAM TECHNOLOGY IN PRIMARY EDUCATION - Yakhshiboeva Sitora Toshpulat kizi (American Journals, 2023)
This article steam education as the education of the future: the scientific theoretical basis of using steam technology in primary education is analyzed. In addition, the need to use STEAM educational technology in primary education, the importance of STEAM educational technology in primary education have been analyzed.
Keywords: STEAM, science, technology, art, math, natural sciences, technology, engineering, mathematics, robotics, elementary education, steam technology, etc.